2017
DOI: 10.1080/09638288.2017.1337817
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mental practice combined with modified constraint-induced therapy on corticospinal excitability, movement quality, function, and activities of daily living in persons with stroke

Abstract: This study confirmed that the combined therapy produces more effective improvement in corticospinal excitability, upper limb function, and performance in daily activities. The combined therapy of mental practice and modified constraint-induced movement therapy could be used as a clinically useful intervention. Implications for rehabilitation Modified constraint-induced movement therapy could be used as an intervention method for people with stroke to make improvements in the quality of movement and performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
0
16
0
4
Order By: Relevance
“…In the 12 studies 11,12,[24][25][26][27][28][29][30][31][32][33] which had medical students or trainees as their population, the primary outcome measures were the Objective Standard Assessment of Technical Skills (OSATS), variations of a Global Rating Scale, independent measures of time taken, precision and accuracy in completion of task or a purpose-built checklist. The remaining studies used task-specific measures such as the Fugl-Meyer assessment for stroke 50,56,61 or broader measures of function such as using a goniometer for range of motion [40][41][42][43] .…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
“…In the 12 studies 11,12,[24][25][26][27][28][29][30][31][32][33] which had medical students or trainees as their population, the primary outcome measures were the Objective Standard Assessment of Technical Skills (OSATS), variations of a Global Rating Scale, independent measures of time taken, precision and accuracy in completion of task or a purpose-built checklist. The remaining studies used task-specific measures such as the Fugl-Meyer assessment for stroke 50,56,61 or broader measures of function such as using a goniometer for range of motion [40][41][42][43] .…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
“…One study showed a low bias risk in selection, performance, detection, attrition, and reporting bias [22]. Seven studies did not mention blinding of participations and personnel and so there were insufficient information to permit the judgement of whether they had a 'low risk' or 'high risk' of bias [5,8,9,[23][24][25][26]. Four studies did not address blinding of the outcome assessment [8,9,23,25], and one study had no blinding of the outcome assessment, and the outcome measurement was likely to be influenced by lack of blinding [26].…”
Section: Risk Of Bias In All Included Rctsmentioning
confidence: 99%
“…The basic components of CIMT include repetitive task/shaping practice with the affected limb, constraint of the unaffected limb, and transfer package [39]. Task practice involves carrying out the usual everyday tasks or activities such as brushing, cooking, washing plates, playing tennis, kicking or throwing a ball, and picking up a cup and taking it to the mouth to drink from it [40,41]. In shaping practice, similar tasks as in task practice are carried out; however, they are broken down into manageable components in which the participant will have to master a component before proceeding to another [40][41][42].…”
Section: Components Of Constraint-induced Movement Therapymentioning
confidence: 99%
“…Task practice involves carrying out the usual everyday tasks or activities such as brushing, cooking, washing plates, playing tennis, kicking or throwing a ball, and picking up a cup and taking it to the mouth to drink from it [40,41]. In shaping practice, similar tasks as in task practice are carried out; however, they are broken down into manageable components in which the participant will have to master a component before proceeding to another [40][41][42]. For example, when a participant is to learn how to pick up a cup and take it to the mouth to drink from it, he will be taught to learn how to grasp the cup, then pick it up, and the rest follows.…”
Section: Components Of Constraint-induced Movement Therapymentioning
confidence: 99%
See 1 more Smart Citation